2020
DOI: 10.3390/ma13112459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZrB2 on Microstructure and Properties of Steel Matrix Composites Prepared by Spark Plasma Sintering

Abstract: In this study, four composites with different ZrB2 content were made by the Spark Plasma Sintering (SPS/FAST) technique. The sintering process was carried out at 1373 K for 5 min under an argon atmosphere. The effect of ZrB2 reinforcing phase content on the density, microstructure, and mechanical and tribological properties of composites was investigated. The results were compared with experimental data obtained for 316L austenitic stainless steel without the reinforcing phase. The results showed that the ZrB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A slight difference in the results of the friction coefficient and the wear coefficient (specific wear rate) may result from the different process of the manufacture of the dual-phase matrix and/or from the use of a different HPHT sintering method (7.5 GPa, 1779 K). The obtained value of the wear coefficient is still much lower than the value obtained for 316L austenitic stainless steel and composite made by SPS [ 64 ], C45 steel (AISI 1045) [ 65 ], NiAl alloy or NiAl self-lubricating matrix composite with the addition of graphene (improving the tribological properties of the composite) made by SPS [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…A slight difference in the results of the friction coefficient and the wear coefficient (specific wear rate) may result from the different process of the manufacture of the dual-phase matrix and/or from the use of a different HPHT sintering method (7.5 GPa, 1779 K). The obtained value of the wear coefficient is still much lower than the value obtained for 316L austenitic stainless steel and composite made by SPS [ 64 ], C45 steel (AISI 1045) [ 65 ], NiAl alloy or NiAl self-lubricating matrix composite with the addition of graphene (improving the tribological properties of the composite) made by SPS [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these methods, the SPS (Spark Plasma Sintering) method is the most widespread. This technology allows for the obtaining of a wide range of materials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typical reinforcements of composites are carbides (TiC, SiC, B 4 C), oxides (ZrO 2 , TiO 2 , Al 2 O 3 , SiO 2 ), nitrides (Si 3 N 4 , BN) and borides (TiB 2 , ZrB 2 ) [ 8 , 9 , 10 , 11 ]. Very vivid interest in the use of zirconium diboride (ZrB 2 ) as a reinforcing phase for metal matrix composites results from a unique combination of physical and mechanical properties offered by this ceramic material [ 12 , 13 , 14 , 15 ]. The beneficial properties of zirconium diboride include high melting point (3245 °C), high hardness (>2200 HV), excellent thermal conductivity (57.9 W/mK) and electrical conductivity (1 × 10 7 S/m).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the composite microstructure showed homogeneous distribution of TiB 2 in the steel matrix. Sulima et al [ 15 ] investigated the effect of the content of ZrB 2 on the density, microstructure and properties of composites based on 316 L austenitic stainless steel matrix. With the increasing content of ZrB 2 , an increase in Young’s modulus and hardness was obtained.…”
Section: Introductionmentioning
confidence: 99%